Respostas
respondido por:
2
Explicação passo-a-passo:
5x-8-(3x+9)=-(x+2)
5x-8-3x-9=-x-2
5x-3x-8-9=-x-2
2x-17=-x-2
2x+x=-2+17
3x=15
x=15/3
x=5
8+(x-3)=6-(x+8)
8+x-3=6-x-8
x+5=-x-2
x+x=-2-5
2x=-7
x=-7/2
Espero ter ajudado!
respondido por:
2
Resposta:
5x - 8 - (3x + 9) = - (x + 2) ⇒ 5x - 8 - 1.(3x + 9) = - 1.(x + 2)
5x - 8 - 3x - 9 = - x - 2
Agrupe os termos semelhantes e efetue:
5x - 3x + x = - 2 + 8 + 9
3x = 15
x = 15 ÷ 3
x = 5
8 + (x - 3) = 6 - (x + 8) ⇒ 8 + 1.(x - 3) = 6 - 1.(x + 8)
8 + x - 3 = 6 - x - 8
agrupe os termos semelhantes e efetue:
x + x = 6 - 8 - 8 + 3
2x = - 7
x = -7 ÷ 2
ou x = - 3,5
Perguntas similares
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás